2013
DOI: 10.1007/s13277-013-1044-0
|View full text |Cite
|
Sign up to set email alerts
|

Cell surface nucleolin is crucial in the activation of the CXCL12/CXCR4 signaling pathway

Abstract: Recently, CXCL12-CXCR4 has been focused on therapeutic strategies for papillary thyroid carcinoma (PTC) and other cancers. At the same time, cell surface nucleolin is also over-expressed in PTC and others. Interestingly, a few reports suggest that either CXCR4 or cell surface nucleolin is a co-receptor for HIV-1 entry into CD4+ T cells, which indicates that there is a relationship between CXCR4 and nucleolin. In this study, antibody and siRNA were used to identify effects of cell surface nucleolin and CXCR4 on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…CD4 and CXCR4/CCR5, through co-ordinated interactions with heparan sulfate proteoglycans and cell-surface-expressed NCL [7] . NCL was found in cellular fractions containing the HIV genome, viral matrix and reverse transcriptase as well as in cross-linked complexes with CD4 and CXCR4/CCR5 at the cell membrane, supporting its potential role in viral entry [8] , [9] . Cell-surface NCL is markedly downregulated immediately after HIV entry into permissive cells as a consequence of its translocation into the cytoplasm [8] .…”
Section: Introductionmentioning
confidence: 80%
“…CD4 and CXCR4/CCR5, through co-ordinated interactions with heparan sulfate proteoglycans and cell-surface-expressed NCL [7] . NCL was found in cellular fractions containing the HIV genome, viral matrix and reverse transcriptase as well as in cross-linked complexes with CD4 and CXCR4/CCR5 at the cell membrane, supporting its potential role in viral entry [8] , [9] . Cell-surface NCL is markedly downregulated immediately after HIV entry into permissive cells as a consequence of its translocation into the cytoplasm [8] .…”
Section: Introductionmentioning
confidence: 80%
“…It controls the metabolism of DNA and RNA in the nucleolus (44,45), shuttles proteins into the nucleus (46), provides posttranscriptional regulation of strategic mRNAs in the cytoplasm (47,48), and serves as a ligand for proteins, such as midkine and the heparin-binding growth-associated molecule, on the cell surface (49). NCL is also involved in the proliferation of many types of cancer (34,(50)(51)(52) and serves as a prognosis marker and therapeutic target for cancer treatment (53)(54)(55). Furthermore, NCL also participates in the pathogenic mechanism and mediates the replication of several viruses and/or serves as a cell surface receptor for Escherichia coli O157 (56), Helicobacter pylori (57), RSV (28), adeno-associated virus type-2 (AAV-2) (58), coxsackie B virus (59), and HIV (29).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that NCL inhibition by siRNAs or anti-NCL aptamers affects cell viability, proliferation, and migration (14,19,(37)(38)(39)(40)(41)(42)(43). To assess the effects of 4LB5 on cell viability and proliferation, we performed a dose-response (0.9-240 nM) experiment using the scFv on MDA-MB-231 triple-negative breast cancer (TNBC) cells at different time points (24,48, and 72 h).…”
Section: Significancementioning
confidence: 99%